Misinterpreting Paced Heart Rhythms: A Case Report. Issue 14 (December 2020) - Luan-Erfe, Betty M.; Sweitzer, BobbieJean; Soghikian, Max O.; Stecker, Eric C.; Schulman, Peter M.
Abstract : We describe 2 cases in which failure to properly interpret paced heart rhythms in patients with cardiac implantable electronic devices (CIEDs) undergoing surgery resulted in adverse consequences including unnecessary invasive procedures, surgical delays, and patient dissatisfaction. Both cases occurred even though experienced clinicians were involved, and all perioperative recommendations were followed. Although it is sometimes argued that anesthesiologists are not directly responsible for CIED management, they are often held accountable when problems arise. These cases reinforce the need for anesthesiologists to not only adhere to all key practice recommendations but to also understand CIED functions and common pitfalls.